Postcolonial Ecocriticism in Avatar: The Way of Water: Unveiling Environmental and Cultural Struggles - Martin, Dominic Thomas; Nainggolan, Maria Gabyriel Bernadetta; Tatemba, Filmorevo Jesse Lincoln; Maukary, Brandon Ezra; Patricia, Catherine (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2025)
This study investigates the postcolonial ecocritical dimensions of James Cameron’s Avatar: The Way of Water (2022), focusing on the tension between the Na’vi (colonized) and the Resources Development Administration (RDA) (colonizer). Drawing on Nixon’s (2011) concept of slow violence and Ashcroft, Griffiths, and Tiffin’s (2002) analysis of imperial dominance, using a qualitative method, the study explores how the film portrays cultural erasure, environmental harm, and resilience. The Na’vi exemplify spiritual connection and ecological respect, while the RDA’s militarized extractive practices reflect unchecked capitalist exploitation. Through a synthesis of film analysis and theoretical insights, this article reveals the broader implications of postcolonial ecocriticism for understanding cultural survival and environmental justice. As the results: 1) The Na’vi endure cultural erasure and ecological harm yet demonstrate resilience through a deep spiritual bond with their environment. 2) The RDA embodies destructive imperialism, deploying militarized technology to extract resources without regard for cultural or ecological welfare. 3) The film’s portrayal of conflict fosters critical reflection on postcolonial ecocriticism, underscoring the need to address the interlinked crises of environmental exploitation and cultural marginalization. By examining Avatar: The Way of Water through a postcolonial ecocritical lens, this study highlights the urgency of integrating cultural and environmental advocacy. It is anticipated that these findings will encourage further scholarly discourse on how literary and cinematic narratives can galvanize both academic and public engagement in dismantling exploitative power structures and championing ecological stewardship.